Language Style Used in the Body of Truck : Grammatical Fluidity and Social Function - Nur Hidayah; Slamet Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Style in a language is frequently used to bring up the intention between the writer and the reader as a real interaction between the speaker and the hearer. Therefore, the phenomenon of language style used in the body of the truck is rewarding to convey different information that presents specific messages. To build a message that relates to social life, the words need context in the view of pragmatics in which the role of semantic meaning is needed as well inflicts the humor sense as regards the social function. In discovering the analysis, a qualitative approach is required for the research. The result shows three language styles appear on words in the body of the truck namely formal style, informal style, and colloquial style. Then, elaborate language meaning in the side of context in pragmatic. The result indicates that physical, epistemic, linguistic, and social contexts are beneficial to point out the message of words on the body truck. Finally, this study found the extent of semantic meaning from words on the body truck relates to social life which contains senses relation of analytic, synthetic, and contradictory. This may suggest that delivering messages in the written mode can be beneficial to the reader especially if it conceives a sense of humor which produce different stereotypes inside the language and is connected through social life.